Clinico-radiological and histopathological study of ovarian masses at a tertiary care centre - Monica K., Shravya; P., Rathnamma; R., Kalyani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Counselling and rapid referral to a specialised facility might be improved with the use of a scoring system that could diagnose ovarian cancer. The relative simplicity of the Risk of Malignancy Index (RMI) scoring technique and the ease with which it may be applied make it a strong candidate to use as a primary diagnostic tool for individuals with pelvic masses. Methods: Prospective observations study conducted on women diagnosed with ovarian mass by clinical examination and confirmed by ultrasonography, undergoing surgery at RL Jalappa Hospital, Kolar from January 2021 to December 2022. Histopathological report was considered as Primary outcome parameter. Age group, Parity, Menstrual history, Risk Malignancy Index, etc., were considered as explanatory parameters. Results: A total of 40 subjects are included among which 22.50% are aged ≤40 years and 77.50% are aged >40 years. Using a cut off of 25, majority (88.2%) of those with malignancy had RMI≥25 and in benign histopathology report 56.5% had ≥25 RMI. Histopathology report, there was a statistically significant (p<0.05) difference in RMI values. The RMI had a sensitivity of 88.24% in predicting malignancy with specificity 43.48%, positive predictive value 53.57%, negative predictive value 83.33% with a total diagnostic accuracy of 62.50%. Conclusions: Results from RMI and histopathology correlate positively. The results of this research show that RMI is a reliable and practicable method for assessing patients with pelvic masses at the commencement of therapy and identifying those who are good candidates for centralised surgical treatment.